2014
DOI: 10.1371/journal.pone.0100873
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pravastatin Prevents Altered Fetal Brain Development in a Preeclamptic CD-1 Mouse Model

Abstract: ObjectiveUsing an animal model, we have previously shown that preeclampsia results in long-term adverse neuromotor outcomes in the offspring, and this phenotype was prevented by antenatal treatment with pravastatin. This study aims to localize the altered neuromotor programming in this animal model and to evaluate the role of pravastatin in its prevention.Materials and MethodsFor the preeclampsia model, pregnant CD-1 mice were randomly allocated to injection of adenovirus carrying sFlt-1 or its control virus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…This is the first study examining the role of sFlt-1 on soft neurologic signs. Our data is in agreement with a mouse model of pre-eclampsia induced by pregnancy-specific overexpression of sFlt-1, where offspring displayed impairments in balance and coordination, and was prevented with maternal pravastatin treatment (Carver et al, 2014). These findings may transform our understanding of the pathophysiologic role of angiogenesis in altering the soft neurologic signs endophenotype, with the potential for novel therapeutic avenues.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is the first study examining the role of sFlt-1 on soft neurologic signs. Our data is in agreement with a mouse model of pre-eclampsia induced by pregnancy-specific overexpression of sFlt-1, where offspring displayed impairments in balance and coordination, and was prevented with maternal pravastatin treatment (Carver et al, 2014). These findings may transform our understanding of the pathophysiologic role of angiogenesis in altering the soft neurologic signs endophenotype, with the potential for novel therapeutic avenues.…”
Section: Discussionsupporting
confidence: 90%
“…Only a few studies have looked at the effects of angiogenesis on brain structure. A mouse model of pre-eclampsia with sFlt-1 overexpression demonstrated brain structural impairments in offspring, an effect that was attenuated with maternal pravastatin treatment (Carver et al, 2014). A similar study in humans, offspring of pre-eclamptic mothers with elevated sFlt-1 showed brain structural and vascular changes compared to controls (Ratsep et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Interestingly, pre-eclampsia and other pregnancy complications have been associated with an increased risk for schizophrenia in adults, and can have additive effects to genetic factors (Dalman et al , 1999, 2001; Cannon et al , 2000). Additionally, it was demonstrated using an animal model that offspring from pre-eclamptic mothers with adenoviral elevated sFlt-1, had a sex-specific reduction in brain volume that was prevented with prenatal pravastatin treatment (Carver et al , 2014). When taken together, this evidence supports a model for genetic vulnerability and obstetrical complication having an additive effect that may result in the development of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, a number of authors have indicated the potential utility of statins in treating PE (113, 545, 12031213), and pravastatin has been the subject of a number of favorable studies (545, 1204, 1206, 1209, 1211, 1214, 1215), including in humans (1204, 12161218). Pravastatin seems more than ripe for a proper, randomized clinical trial (1203).…”
Section: Prevention Strategiesmentioning
confidence: 99%